Simpler the future of government - Sunstein, Cass R. (New York Simon & Schuster, 2013)
Simpler government arrived four years ago. It helped put money in your pocket. It saved hours of your time. It improved your children?s diet, lengthened your life span, and benefited businesses large and small. It did so by issuing fewer regulations, by insisting on smarter regulations, and by eliminating or improving old regulations. Cass R. Sunstein, as administrator of the most powerful White House office you?ve never heard of, oversaw it and explains how it works, why government will never be the same again (thank goodness), and what must happen in the future.
Includes bibliographical references and index.
Keywords: POLITICAL SCIENCE / Government / General